2006
DOI: 10.1128/ec.00028-06
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Copper-Inducible Promoter for Use in Ectopic Expression in the Fungal Pathogen Histoplasma capsulatum

Abstract: Despite the existence of a number of genetic tools to study the fungal pathogen Histoplasma capsulatum, strategies for conditional gene expression have not been developed. We used microarray analysis to identify genes that are transcriptionally induced or repressed by the addition of copper sulfate (CuSO 4 ) to H. capsulatum yeast cultures. One of these genes, CRP1, encodes a putative copper efflux pump that is significantly induced in the presence of CuSO 4 . The upstream regulatory region of CRP1 was suffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
(56 reference statements)
3
13
0
Order By: Relevance
“…Several inducible promoters developed in other systems rapidly trigger expression of a target gene in response to an inducer with a subsequent decrease in gene expression over time. For example, a copper-inducible promoter in Histoplasma capsulatum (5) showed the same regulation pattern as the ZEA-inducible promoter analyzed in this study. In order to overcome these types of side effects in conditional expression systems, other promoters need to be identified that can be differentially or constitutively induced.…”
Section: Vol 76 2010 Zearalenone-inducible Promoter 3091supporting
confidence: 66%
See 1 more Smart Citation
“…Several inducible promoters developed in other systems rapidly trigger expression of a target gene in response to an inducer with a subsequent decrease in gene expression over time. For example, a copper-inducible promoter in Histoplasma capsulatum (5) showed the same regulation pattern as the ZEA-inducible promoter analyzed in this study. In order to overcome these types of side effects in conditional expression systems, other promoters need to be identified that can be differentially or constitutively induced.…”
Section: Vol 76 2010 Zearalenone-inducible Promoter 3091supporting
confidence: 66%
“…Further, a recombinant bacterium strain of Staphylococcus aureus had a higher sensitivity to metal but showed severe growth inhibition at 100 nM Cd (33). Similarly, a recombinant H. capsulatum strain containing lacZ that was controlled by a copper-inducible promoter showed ␤-galactosidase activity at 1 to 500 M CuSO 4 (5). The recombinant G. zeae strains developed in this study had a detection range of 3 to 1,500 M ZEA.…”
Section: Vol 76 2010 Zearalenone-inducible Promoter 3091mentioning
confidence: 59%
“…Both Wor1 and Ryp1 bind to their own promoters, raising the possibility that Ryp1, like Wor1, may induce a self-sustaining feedback loop that promotes RYP1 transcript accumulation under appropriate conditions. Indeed, we observed that in particular transformants, ectopic expression of RYP1 under the control of a copper-inducible promoter (38) resulted in high-level induction of the endogenous RYP1 transcript (data not shown). However, this phenomenon was not consistently observed, suggesting that the switch between potential expression states may be more complex than a simple positive-feedback loop.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it may not contain sugar-regulated promoters, which are widely used for inducible gene expression in its relative, C. crescentus (18), and many other bacteria. Prompted by the successful application of heavy metal-inducible expression systems in other organisms (19)(20)(21)(22), we investigated whether this strategy also would be applicable to H. neptunium. In doing so, we specifically focused on copper and zinc, two heavy metals with moderate toxicity that also serve as essential trace elements (23,24).…”
Section: Identification Of Heavy Metal-inducible Promotersmentioning
confidence: 99%